2021
DOI: 10.3390/su13073704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Monitoring of Urban Public Greenspace Planning Using Landscape Metrics in Kunming

Abstract: Urban greenspace planning plays a crucial role in improving the quality of human settlements and the living standard of citizens. Urban public greenspace (UPGS) is an important part of urban greenspaces. Existing literature rarely includes a scientific evaluation of greenspace plans (including of UPGS) and plan implementation effects. To bridge this gap, this study evaluated and monitored the UPGS plan enacted in 2010 in Kunming, China. Object-based image classification and visual interpretation of satellite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…The first deals with the difference between the terms green place and public green place, green network and public green network. Foreign authors do not distinguish these terms [13,19,31] because, by default, all green places in the city serve not only ecological but also social life. However, the case study of Russian cities indicates the necessity of a clear definition of the lands that can be included in the green city network because not all green places in Russian cities are in social use on the one hand, and not all public spaces can be integrated into city green backbone [16,36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first deals with the difference between the terms green place and public green place, green network and public green network. Foreign authors do not distinguish these terms [13,19,31] because, by default, all green places in the city serve not only ecological but also social life. However, the case study of Russian cities indicates the necessity of a clear definition of the lands that can be included in the green city network because not all green places in Russian cities are in social use on the one hand, and not all public spaces can be integrated into city green backbone [16,36].…”
Section: Discussionmentioning
confidence: 99%
“…Today, worldwide, the evaluation of the city's territorial space development mainly uses mathematic models of collecting and analyzing both qualitative and quantitative data [7,13,17,19,31,32,34,35]. In Russia, a lack of quantitative data makes qualitative data analysis more usual [5,9,11,15,16,21,36].…”
Section: Recreational and Urban Green Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In urban environments, studies using landscape metrics have identified a low connectivity of green and blue spaces, partially due to the dominance of the built environment in cities [17]. Such dominance of the built environment has a detrimental effect on biodiversity due to a lack of habitat [18,19].…”
Section: Introductionmentioning
confidence: 99%